La violence exercée contre les jeunes filles autochtones : le problème, sa face cachée, les sources d’espoir et les interventions possibles - Down, Pamela J. (Violences faites aux femmes, 2008)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; autochtones; canada; cours; disparitions des filles et des femmes autochtones; périodes historiques; racisme; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; trs3500; violences; violences envers les femmes*; violences sexistes et sexuelles

L'association des femmes inuites du Nunavik Saturviit : porteuses d'espoir et de paix - Koperqualuk, Lisa Q. (2008)
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; environnement; famille; féminisme autochtone; inégalités; maternité; nunavik; pol4105; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; violences

Globalization as Racialized, Sexualized Violence THE CASE OF INDIGENOUS WOMEN - Kuokkanen, Rauna (International Feminist Journal of Politics, 2008)
In my article, I suggest that indigenous women are among the hardest hit by economic globalization – the expansion of markets, trade liberalization and cheapening of labour – and that globalization represents a multifaceted violence against indigenous women. I consider this with the help of two examples. First, I discuss the largely ignored case of missing and murdered Aboriginal women in Canada and how the interlocking systems of oppression (colonization, patriarchy and capitalism) are further intensified by globalization. Second, I examine the death of a Hopi woman, Private Piestewa, in the context of militarization, history of colonization and globalization. I analyse these examples in an intersectional framework that reveals the links between colonization, patriarchy and capitalism all of which inform the current processes of globalization.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; armée états-unienne; canada; capitalisme; cours; discipline; féminicide; globalisation; histoire et politique; intersectionnalité; militarisation; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; science politique; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; états-unis

Firekeepers of the twenty-first century: First Nations women chiefs - Voyageur, Cora Jane (McGill-Queen's Native and northern series, 2008)
A quiet revolution is occurring in Canada's First Nations communities, with changes taking place on social, political, and economic fronts and a significant redistribution of power. Changes to the Indian Act in 1951 paved the way for women to become officially involved in reserve politics, and with governments responding to the demand of First Nations for self-government, positions once held exclusively by men are now being filled by women. Beginning with Elsie Knott, the first female chief in Canada, Cora Voyageur presents the lives of sixty-four of the ninety women chiefs who have assumed the traditionally male role of elected First Nations leadership. Using a range of qualitative research strategies, surveys, participant observation, interviews, and discussions with focus groups, Voyageur presents the colonial histories behind the issues that contemporary Aboriginal communities struggle with and delineates the resulting leadership dilemmas for chiefs, while also articulating a story that is unique to First Nations women. Voyageur asks women chiefs about what inspired them to become leaders, how they've maintained their priorities, and the personal and professional costs and rewards involved in their positions. Firekeepers of the Twenty-First Century is a groundbreaking work that examines the experiences of women as they negotiate multiple roles and navigate the worlds of gender, race, and reserve politics.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; entretien; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; féminisme décolonial; gouvernance; histoire et politique; militance; pol4105; pouvoir; premier cycle; premières nations; périodes historiques; régions géographiques; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques